Respuesta :

Using Elimination Method:

Equation 1: 4x + 5y = -4

Equation 2: 4x + 3y = 12


First step is elimination one of your variable, the best variable to eliminate here is x. (Why? Because both has equation had 4x and easy to eliminate). But to eliminate, first variable need to be - and other +.

So change or multiply one of the equation by -1, I will pick equation 2:

(4x + 3y = 12) * -1  


4x + 5y = -4

-4x - 3y = -12

-----------------------

0x + 2y = -16

y = -16 / 2

y = -8


Now you got y-value, to get x, substitute y with -8 in any one of the equation. I will pick equation 2:

4x + 3y = 12

4x + 3(-8) = 12

4x - 24 = 12

4x = 12 + 24

4x = 36

x = 36/4

x = 9


Solution: (9, -8)